Eating, Sleep, and Social Patterns as Independent Predictors of Clinical, Metabolic, and Biochemical Behaviors Among Elite Male Athletes: The EROS-PREDICTORS Study - Cadegiani, Flavio A.; Kater, Claudio E. (Frontiers in Endocrinology, 2020)
Objectives: Physiological hormonal adaptions in athletes and pathological changes that occur in overtraining syndrome among athletes are unclear. The Endocrine and Metabolic Responses on Overtraining Syndrome (EROS) study evaluated 117 markers and unveiled novel hormonal and metabolic beneficial adaptive processes in athletes. The objective of the present study was to uncover which modifiable factors predict the behaviors of clinical and biochemical parameters and to understand their mechanisms and outcomes using the parameters evaluated in the EROS study. Methods: We used multivariate linear regression with 39 participants to analyze five independent variables—the modifiable parameters (caloric, carbohydrate, and protein intake, and sleep quality and duration of concurrent cognitive activity) on 37 dependent variables— that were elected among the parameters evaluated in the EROS study. Results: Carbohydrate intake predicted quick hormonal responses to stress and improved explosive responses during exercise. Protein intake predicted improved body composition and metabolism and caloric intake, regardless of the proportion of macronutrients, predicted muscle recovery and alertness in the morning. Sleep quality predicted improved mood and excessive concurrent cognitive effort in athletes under intense training predicted impaired metabolism and libido. Conclusions: The results support the premise that eating, sleep, and social patterns modulate metabolic and hormonal function, clinical behaviors and performance status of male athletes, and should be monitored continuously and actively to avoid dysfunctions.